Language and infant mortality in a large canadian province - Auger, Nathalie; Bilodeau-Bertrand, M.; Costopoulos, A. (Public Health, 2016)
Objectives Infant mortality in minority populations of Canada is poorly understood, despite evidence of ethnic inequality in other countries. We studied infant mortality in different linguistic groups of Quebec, and assessed how language and deprivation impacted rates over time. Study design Population-level study of vital statistics data for 1,985,287 live births and 10,283 infant deaths reported in Quebec from 1989 through 2012. Methods We computed infant mortality rates for French, English, and foreign languages according to level of material deprivation. Using Kitagawa's method, we evaluated the impact of changes in mortality rates, and population distribution of language groups, on infant mortality in the province. Results Infant mortality declined from 6.05 to 4.61 per 1000 between 1989–1994 and 2007–2012. Most of the decline was driven by Francophones who contributed 1.39 fewer deaths per 1000 births over time, and Anglophones of wealthy and middle socio-economic status who contributed 0.13 fewer deaths per 1000 births. The foreign language population and poor Anglophones contributed more births over time, including 0.08 and 0.02 more deaths per 1000 births, respectively. Mortality decreased for Francophones and Anglophones in each level of deprivation. Rates were lower for foreign languages, but increased over time, especially for the poor. Conclusions Infant mortality rates decreased for Francophones and Anglophones in Quebec, but increased for foreign languages. Poor Anglophones and individuals of foreign languages contributed more births over time, and slowed the decrease in infant mortality. Language may be useful for identifying inequality in infant mortality in multicultural nations.

Quand le manque d’accès aux services en français revictimise les femmes victimes de violence conjugale et leurs enfants - Lapierre, Simon; Coderre, Cécile; Côté, sabelle; Garceau, Marie-Luce; Bourassa, Chantal (Reflets, 2014)
Cet article s’appuie sur les résultats d’une recherche réalisée en Ontario et au Nouveau-Brunswick, visant à documenter l’accès aux services en français pour les femmes francophones victimes de violence conjugale et pour leurs enfants. S’appuyant sur les résultats de la première phase d’une recherche-action réalisée en partenariat avec des chercheuses universitaires et des milieux communautaires, les données démontrent que ces femmes sont confrontées à des réalités particulières et que les lacunes dans l’accès aux services en français compromettent leur bien-être, leur santé et leur sécurité. Ces lacunes ont également des impacts sur le bien-être, la santé et la sécurité de leurs enfants. Considérant ces impacts, le manque d’accès aux services en français peut être perçu comme une forme de revictimisation des femmes. Mots-clés : services en français, violence conjugale, violence faite aux femmes, enfants exposés à la violence conjugale, santé des femmes, sécurité des femmes, santé des enfants, sécurité des enfants

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)
fs-ref-orig: Richardson, M. et Ledoux, J.-J. (2018). Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes. Council for Anglophone Magdalen Islanders. fs-code-orig: Richardson-2018